Self-Esteem: Orientasi Karakter dalam Pembelajaran Sejarah - Yoan Mareta; Robit Nurul Jamil (UIN Imam Bonjol Padang, 2022)
Historical education in the context of learning must offer valuable solutions to overcoming character problems. This urgency should be understood by all history educators as a mandate that history is a heritage of values, it is necessary to absorb values, so that the goal of history in forming wise human beings will be achieved. Self-esteem is one aspect of personality that has an important role and has a major influence on individual attitudes and behavior. This value is very important to support the national identity and character of students. The dynamics of modernization requires a container of values in cultural transformation, so that students who are citizens have filters to sort out the impact of the current of modernization. The research method used is a qualitative paradigm (qualitative description). The results of the discussion: 1) Explanation of self-esteem in character building; 2) The position of learning history in growing self-esteem. The conclusions of this study include: 1) Self-esteem has a major influence on the formation of students' character; 2) History learning is a bridge for students' character growth; 3) Character building is very difficult in national education if learning is not oriented to certain values.